Representation of Masculinity in the Poetry Anthology "Barista tanpa Nama" by Agus Noor - Ulya, Chafit; Rubiyanto, Bhian Cahya W.; Putri, Ulfa Rizqi; Noreewec, Andreas (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Gender equality has been an intriguing topic, particularly in the modern era. Modernization has given new meaning to the relational dynamics between men and women, leading to changes in the concept of masculinity. In this regard, the present research discussed the representation of masculinity in the poetry anthology “Barista tanpa Nama” by Agus Noor. This study employed a qualitative descriptive method to identify the aspects of masculinity in poetry, referring to Janet Saltzman Chafetz's theory. Seven characteristics of masculinity were examined in this study: (1) physical, (2) functional, (3) sexual, (4) emotional, (5) intellectual, (6) interpersonal, and (7) other personal traits. Based on the research findings, it was observed that the anthology “Barista tanpa Nama” by Agus Noor encompassed six out of the seven characteristics. Among these six, the sexual aspect emerged as the most dominant feature. However, it did not primarily focus on men driven by sexual desires but reflected those who prioritize care, attention to women, and genuine expressions of love without expectations. Thus, the representation of masculinity in the poetry anthology “Barista tanpa Nama” could be seen as a manifestation of a man's care, affection, and patience towards women.